Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai di Dinas Koperasi dan Usaha Mikro Kota Malang - Maria Yulita Dhone; Ondi Asroni (JURNAL AKADEMISI VOKASI, 2024)
The rapid development of globalization has had an impact on changes in the order of people's lives. The rapid and inevitable development of globalization demands an increase in the quality of human resources. Globalization not only has an impact on society but also has an impact on government institutions as agencies that provide services to society. The changes that occur require agencies to continue to maintain and improve their human resources so that they are able to compete and continue to provide the best service to the community. This research aims to determine the influence of leadership style and work motivation on employee performance. The population that will also be used as a sample in this research is all employees at the Malang City Cooperatives and Micro Enterprises Department, totaling 34 people. The approach taken in this research is a quantitative descriptive approach, namely research that uses numbers starting from data collection, interpretation and appearance of results (Arikunto, 2010). Reliability and validity testing shows that the statements used in each variable are declared reliable and valid. Classical assumption testing includes the multicollinearity test, heteroscedasticity test and normality test. This research was conducted to determine the influence of leadership style and work motivation on employee performance.